Pengembangan Alat Bantu Pemanggil Penyandang Tunarungu Menggunakan Library Pocketsphinx Berbasis Android (Studi Kasus PSLD Universitas Brawijaya) - Nurul Huda Abdullah; Mahardeka Tri Ananta; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Smartphone can help activities people of disabilitie, among others, is to seek information, self-existence and eliminate burnout. But smartphones can be used also to help communicate between normal people and people with disabilities, one of which is calling people with hearing disability. If a normal person wants to call a person with hearing impairment, he or she should usually tap the shoulder or turn on the light switch to attract the attention of the deaf. But with the presence of sensors embedded in smartphones, normal people can easily call the deaf. To facilitate the calling of the deaf person then designed and implementation of an application converts voice into text. This app works if there is a voice calling the name of a person with hearing impairment, so the smartphone belonging to the deaf person can give a vibrating notification. To implement the application need to use the library to convert the sound into text that is pocketsphinx library. The application also needs to be implemented in the background service so that users can open other applications / programs without interrupting the application being run. This app also uses vibrate notifications to give notifications to app users if anyone calls This Aplication can recognize sound up to 4 meters.. Then the user response to the application tested by usability testing obtained 76.25% for caller and 81.18% for the deaf. This shows that the application is good and successful.